Temporal fine structure: associations with cognition and speech-in-noise recognition in adults with normal hearing or hearing impairment. - Ellis, Rachel J.; Rönnberg, Jerker (International Journal of Audiology, 2022)
To investigate associations between sensitivity to temporal fine structure (TFS) and performance in cognitive and speech-in-noise recognition tests. A binaural test of TFS sensitivity (the TFS-LF) was used. Measures of cognition included the reading span, Raven's, and text-reception threshold tests. Measures of speech recognition included the Hearing in noise (HINT) and the Hagerman matrix sentence tests in three signal processing conditions. Analyses are based on the performance of 324/317 adults with and without hearing impairment. Sensitivity to TFS was significantly correlated with both the reading span test and the recognition of speech-in-noise processed using noise reduction, the latter only when limited to participants with hearing impairment. Neither association was significant when the effects of age were partialled out. The findings are consistent with previous research in finding no evidence of a link between sensitivity to TFS and working memory once the effects of age had been partialled out. The results provide some evidence of an influence of signal processing strategy on the association between TFS sensitivity and speech-in-noise recognition. However, further research is necessary to assess the generalisability of the findings before any claims can be made regarding any clinical implications of these findings.